Primary peritoneal serous psammocarcinoma, rare variant: A case report - Srujan Kancharla; Anne Alaniz; Pulin Kothari; Stacy Norton (Gynecologic Oncology Reports, 2023)
Psammocarcinoma is a rare form of serous carcinoma of the ovary or peritoneum characterized by extensive psammoma body formation seen on histology. A 49-year-old obese woman, gravida 1 para 1 with poorly controlled type 2 diabetes, presented with a history of menorrhagia. She was diagnosed with both leiomyomata and simple endometrial hyperplasia without atypia in the office. Consultation with gynecological oncology and primary gynecologist resulted in a planned hysterectomy with bilateral salpingo-oophorectomy.Laparoscopic hysterectomy and bilateral salpingo-oophorectomy were performed by primary gynecologist. Intraoperative survey of pelvis found concerning nodular lesions seen in posterior cul-de-sac. Lesions were excised and sent for frozen section. Pathology showed invasive peritoneal epithelial implant with psammomatous calcifications. Gynecological oncologist stand-by was called in and proceeded with surgical debulking and staging procedure.Post operatively, the patient has been diagnosed with primary peritoneal low grade serous psammomacarcinoma stage III A2. Her case has been presented to tumor board for multidisciplinary management and is now undergoing adjuvant hormonal therapy utilizing letrozole with chest, abdomen, and pelvic CT scans every 6 months. Standardized protocols are hindered by the rarity of this tumor. Benefits for this oncologic diagnosis are not clearly understood due to the rarity of this tumor.The significance of this case presentation is to highlight the multidisciplinary approach to the workup, diagnosis, treatment (both surgical and medical) and follow up of a rare gynecologic oncologic case. While the surgical team was expecting to find at most significant pathology, an endometrial carcinoma, a rarer primary peritoneal carcinoma was found. Due to the pre surgical planning, and intraoperative teamwork of the pathology, gynecology and oncology teams, this patient received the individualized and disease specific needed surgical and medical care warranted by her unique diagnosis.